Analisis Karakteristik Hidraulis Air Tanah Gambut Berdasarkan Uji Pemompaan (Pumping Test) - Vito Charly; Bambang Sujatmoko; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pumping test was conducted to determine the characteristics of an aquifer transmissivity and storativity values. Pumping test can measure the amount of water from an aquifer so that the potential of groundwater can be determined from any research areas. Pumping test carried out in two stages, first is the productionwell pumping test to observe the drawdown caused by the pumping process and second is recovery test were performed to observe the recharge process of pumped production wells. This research located in Rantau Baru village’s groundwaterwells. Analytical method used is Cooper Jacob method (straight-line method) so that the obtained transmissivity (T) value is 1822,639 m2/day and storativity (S) value is 9,978×10-5. Based on these acquired two parameters, the availability potential of groundwater at this research location is 467,8 m3/day. By identificationof groundwater discharge, the utilization of groundwater at the research locationcan be controlled in order to avoid any ground water depletion.Keyword : Pumping test, drawdown, aquifer, Cooper Jacob